Hubungan Kerawanan Pangan Rumah Tangga, Pengetahuan Gizi Ibu terhadap Status Gizi Balita di Pulau Gili Iyang, Indonesia: Household Food Insecurity, Nutritional Knowledge of Mothers on Nutritional Status among Children Under Five Years in Gili Iyang Island, Indonesia - Prameswari, Atika Anif; Pratiwi, Damai Arum; Mahmudiono, Trias; Prasiska, Danik Iga; Azmy, Ulul; Safaryna, Alifia Merza (Amerta Nutrition, 2025)
Background: Food insecurity in the home and well-informed moms' nutritional understanding can shield children from circumstances that result in low height and body mass index (BMI) for their age. Objectives: The purpose of this study is to ascertain the relationship between food insecurity in the home and mothers' nutritional awareness of the nutritional condition of children under five on Gili Iyang Island. Methods: This study used a cross-sectional method. The nutritional status of the children was assessed using anthropometric measurements. Additionally, data on demographic characteristics, maternal nutrition knowledge, and food insecurity were collected using questionnaires. The study involved 39 mothers/caregivers of children as respondents. Results: Mothers had a low degree of dietary awareness (84.62%). Stunting and wasting rates were 17.95% and 12.82%, respectively. The incidence of stunting decreased with increased nutritional knowledge of mothers (p-value=0.032, r=0.343), and there was a strong positive association between mothers' knowledge of nutrition and children's height-for-age. Nutritional status (HAZ) and household food security were significantly correlated (p-value<0.001). Conclusions: The conclusion was that there was an association between the nutritional knowledge of mothers and the status of children’s nutrition. There was a relationship between household food security and a child’s nutritional status.